ANALISIS KINERJA KEUANGAN PADA DESA LANGIR KECAMATAN KANGAE KABUPATEN SIKKA - Luju, Elisabet; Winarti, Thresia (Jurnal Projemen UNIPA, 2024)
research with the title Analysis of Financial Performance in Langir Village in 2022 and 2023. The aim of this research is to determine the performance of the Langir Village Government for the 2022 and 2024 fiscal years based on the decentralization ratio, Independence Ratio, Dependency Ratio, and Expenditure Effectiveness Ratio. The analytical method used is a qualitative approach. The research results show that the financial performance of the Langir Village Government for the 2022 and 2023 budget years based on the Decentralization ratio is still very low, the financial independence ratio is still very low, the dependency ratio shows that the level of dependence on the central and provincial governments is still very high, while based on the efficiency ratio it is still less efficient. This is caused by delays in signing and spending is still greater than income.